The Study of Anthropometric of Massey Fergusson 400 Extra Tractor - Tiurma Rosita Sinaga; Achwil Putra Munir; Ainun Rohana (Universitas Sumatera Utara, 2015)
Seat is one of the dominant factors to get a job perform conveniently on a four-wheel tractor by operator. It is therefore necessary to design a seat that fits the dimensions of Indonesian’s body in general, as the tractor in Indonesia is made overseas. This research was conducted by measuring the dimensions of the body 100 correspondents that were taken randomly. The data collected were popliteal height, buttock-distance popliteal height, shoulder span, span between the elbow rest position, high elbow resting position, the shoulder height and weight. The results showed that high current cushion was 50 cm high while the proposed was 46 cm. The current length of the cushion was 38.5 cm while the proposed was 46 cm, width of the cushion was currently was 46.5 cm while the proposed was 38.4 cm, high backrest c current was 47.5 cm while the proposed was 23 cm and the proposed was load 60-70 kg. Keywords: tractor, anthropometry, seat